VMware NSX Cookbook : Over 70 recipes to master the network virtualization skills to implement, validate, operate, upgrade, and automate VMware NSX for vSphere - Sangha, Tony; Wibowo, Bayu (Packt Publishing, 2018)
VMware NSX is a software-based networking and security virtualization platform that delivers an operational model of a virtual machine for the network. By virtualizing the network, NSX breaks through current physical network barriers and enables data center operators to achieve better speed and agility with reduced costs.